PENGARUH STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR KESEHATAN REPRODUKSI TENTANG PERSONAL HYGIENE (VULVA) PADA SISWA KEPERAWATAN DI SMK KARTINI KOTA BATAM TAHUN 2017 - Asnari, Yuni; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2017)
The Contextual Teaching and Learing (CTL) is a form of an educational process that resolves to help the students in understanding the academic materials to be learned by relating the subjects to real life contexts comprises personal, social, and cultural life contexts. This study aims to determine the impacts of the CTL method to the learning outcomes, particularly subject on reproductive health concerning the personal hygiene. The research method used in this study was an experimental approach with pretest-posttest one group design. This study was conducted on July 2017 by taking 33 respondents as the sample through total sampling technique. As the research instruments, the researchers made questionnaire and distributed it to the respondents. The data gathered then was analyzed by Kolmogrov-smirnov test.  The result of the study shows that 17 students who had CTL treatment ensued mean score of 84.05 and conventional group of 16 students ensued mean score of 76.31 with p-value 0,000 which was lower than 0,005. In conclusion, it can be decided that there is a significant impact of CTL approach to the students’ learning outcomes on reproductive health subject specifically related to personal hygiene of vulva. At last, it is expected that the female students as the respondents to implement their knowledge and understanding on vulva hygiene in real life contexts.